Model Pembelajaran Two Stay Two Stray dalam Meningkatkan Hasil Belajar Peserta Didik Subtema Perubahan Linkungan di Madrasah Ibtidaiyah - Aswad Fadi; Samrin Samrin; Samsu Samsu (Diniyah: Jurnal Pendidikan Dasar, 2020)
This study aims to improve student learning outcomes through the implementation of the Two Stay Two Stray learning model on the sub-theme of environmental change. This is a classroom action research which consists of 2 cycles. The research subjects were 21 students of class VB MIN 1 Kendari. Data were collected by documentation, learning outcomes tests, and observation. The research findings showed that student learning outcomes on the sub-theme of environmental change can be improved through the implementation of the Two Stay Two Stray learning model. The students' learning mastery in the pre-cycle was 23.80% with an average of 59.14 and increased in the first cycle with 52.38% learning completeness and an average of 63.80 and again increased in the second cycle with 80.95 learning mastery and an average of 71.90.Keywords: Two Stay Two Stray (TSTS), Learning Outcomes of Students, Thematic Learning